Privacy‐preserving grouping proof with key exchange in the multiple‐party setting. Issue 16 (14th July 2016) - Tian, Yangguang; Yang, Guomin; Mu, Yi
Abstract: Grouping proof is a very useful security primitive that can be used to prove the co‐existence of multiple entities in an identification protocol. It can be incorporated into radio frequency identification protocols and used in many practical applications such as pharmaceutical distribution and manufacturing. However, the existing grouping proofs do not support secure key establishment, which is required in order to allow secure communication between the reader and the radio frequency identification tags after the identification process. In this paper, we propose a novel grouping proof with key exchange that allows the reader to establish a secure communication channel with the tags. We define the formal security models for grouping proof with key exchange and prove that the proposed generic protocol can achieve grouping proof soundness, session key security, contributiveness, and tag identity privacy. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, we propose a yoking/grouping proof with key exchange that allows the reader to establish a secure communication channel with the RFID tags. Hence, we prove the co‐existence of multiple entities in an identification protocol.